The Influence of Diary Writing Activities on Academic Writing Skills - Nafeesha, Shahna Fairuz Ahlandyta; Hadiyansyah, Dhuha (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study aims to identify the influence of diary writing habits on writing skills among university students. Diary writing as a routine activity has the potential to improve several aspects of writing skills, such as vocabulary development, sentence structure, critical thinking, and creativity. With the development of technology and an increasingly dynamic lifestyle, diary writing can be an effective alternative in improving writing skills outside the academic context. This study uses a qualitative analysis method by collecting data through in-depth interviews with 15 informants who have regular experience in writing diaries. The data obtained from these interviews were then analyzed to determine the impact of diary writing habits on their writing skills, both in terms of vocabulary mastery, sentence structure, as well as improving critical thinking skills and creativity. The results showed that the habit of writing a diary can enrich students' vocabulary, improve their ability to compose more structured and effective sentences, and develop critical thinking and creativity in writing. In addition, this study also showed that the frequency and intensity of diary writing play an important role in the development of writing skills. The more frequently and consistently students write diaries, the more visible the improvement in their academic writing skills. This research is expected to provide deeper insights into the benefits of diary writing as one of the effective learning methods in the development of writing skills.